Analysis and design of DC-DC converter - Zhou, Mi (Nanyang Technological University, 2019)
Nowadays, electronic products are required to be more powerful with sophisticated functionalities. Designing power management units for such devices becomes more and more challenging. The DC-DC converters are expected to meet all stringent requirements such as fast response speed, high efficiency, high reliability, small footprint, large driving capabilities, wide input, and output voltage ranges, etc. In this work, several methods are proposed to improve the performances of the switched inductor DC-DC converter with varied targeting applications. The conventional linear Pulse-Width Modulation (PWM) control switched inductor DC-DC converter has a slower transient response than the one with nonlinear control, but the advantages in noise immunity, low voltage ripples, and high-efficiency characteristics make the control itself non-replaceable in certain applications. In this work, two alternatives to achieve a fast transient response in PWM DC-DC converter are proposed. The first method makes use of an Active Compensation Capacitor Module (ACM) to replace the conventional passive capacitor, the proposed scheme adaptively increases the slew rate of the transconductance during the transient period by instantaneously reduce the value of the compensation capacitor at the output of the transconductance. The proposed scheme has been applied to a current-mode buck DC-DC converter. The experimental results show output voltage overshoot/undershoot of 25.5 mV/22 mV with 6 s/6.2 s recovery time respectively under 0.5 A load current step. In the experimental results, the proposed converter is proven to achieve the best performance among the prior arts which is summarized in Table 3.3 in Chapter 3. The other method introduces an AC Coupled Feedback (ACCF) connected between the outputs of the converter and the transconductance. With the additional feedback, the transient response has been significantly improved by increasing the compensator’s mid-band gain. Meanwhile, the ACCF circuit helps to manage the converter’s start-up in-rush current, which is usually realized by an extra complicated soft-start circuit in other works. The proposed method is simple to implement while demonstrates great performance in experimental results. A buck converter with the proposed technique has been fabricated using 0.18 μm CMOS process with an active silicon area of 0.573 mm2. Measurement results show that the output voltage increases linearly for a soft-start period of 1050 μs. An excellent load regulation of 0.018 mV/mA is achieved for a load current variation from 50 μA to 1 A in 1 μs. And the output voltage ripples of 60 mV are observed at the load transient period which settles down within 10 μs. A new control methodology for voltage, current and temperature regulation is proposed. The new control methodology can be implemented in either the switching DC-DC converter, LDO, audio amplifier or haptic motor driver for different applications. In this work, a buck converter is implemented with the control methodology to control the charging process of the Lithium-ion battery. The new approach is designed to simultaneously sense and control the temperature of the power transistors and the battery on-chip, which usually requires an off-chip current sensor to sense the battery temperature, and CPU to process the temperature information before send to the control loop for regulation in others’ works. The proposed work achieves the comparable performances as the modern commercial products (regulates the battery voltage, defines the maximum input charging current and adaptively manages the temperature of the Lithium-ion battery) with lesser hardware requirements. It also demonstrates great performance in the simulations.